Rabiah Al-Adawiyah Dalam Konsep Mahabbah dan Al-Ghazali Dalam Konsep Makrifah - Santalia, Indo; Haq, Fitri Maylan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out the concept of mahabbah according to Rabiah al-Adawiyah and the concept of makrifah according to al-Ghazali. This research focuses on these two Sufis because they are Sufism scholars who are famous for their respective concepts. To obtain relevant research results, this research uses data collection techniques or literature study methods. Rabiah al-Adawiyah is very famous among taswwuf as a female poet, her poetry is written as proof that her love for Allah has no limits, so according to her the concept of mahabbah is divided into hubb al-hawa dan hubbun liannaka ahlan lidzaka. Likewise with al-Ghazali, in his concept of makrifah in ma'rifatullah it cannot be reached by the senses or reason, but we arrive at makrifah using the qalb.